Prevalence and Risk Factors of Schistosomiasis among School-Age Children and Adolescents in Zaria, Kaduna State, Nigeria - Tanko A. Nanret; Suchi K. Nanret; Orinya Alfred; Ejembi Joan; Olanrewaju Jimoh; Dimowo C. Palangutde; Ahmed S. Opaluwa; Abdulaziz M. Mukhtar; Medugu Nubua (Darul Yasin Al Sys, 2026)
Nigeria bears the world’s highest burden of schistosomiasis, with school-aged children and adolescents experiencing particularly high prevalence and infection intensity. In Zaria metropolis, the abundance of water bodies and frequent water-contact activities, including irrigation farming and swimming, may increase the risk of transmission. This study aimed to determine the prevalence of schistosomiasis and identify its associated risk factors among school-aged children and adolescents in Zaria metropolis. A community-based cross-sectional study was conducted among individuals aged 6–19 years using a multistage sampling technique to select communities, clusters, and households. Stool and urine samples were collected from eligible participants and examined for ova of Schistosoma species using standard laboratory techniques. Demographic characteristics and potential risk factors were assessed using a structured questionnaire, and the data were analysed using SPSS version 26. A total of 423 participants were recruited from the Biye, Bomo, Wuchichiri, and Kufena communities. The overall prevalence of schistosomiasis was 10.6% (45/423), comprising 9.5% (40/423) urinary schistosomiasis caused by Schistosoma haematobium and 1.2% (5/423) intestinal schistosomiasis caused by Schistosoma mansoni. Frequent water contact through swimming and irrigation farming was significantly associated with increased odds of infection (adjusted odds ratio [AOR] = 2.688, 95% confidence interval [CI]: 1.341–5.386, p = .005), while geographical location was also independently associated with schistosomiasis (AOR = 0.275, 95% CI: 0.102–0.740, p = .011). These findings indicate a high prevalence of schistosomiasis among school-aged children and adolescents in Zaria metropolis and demonstrate the importance of water-contact behaviour and geographical context in sustaining transmission. The study provides epidemiological evidence to support geographically targeted interventions, health education, reduced exposure to infested water bodies, and strengthened schistosomiasis prevention and control programmes.